The Safety of Non‐immunogenic Recombinant Staphylokinase in Elderly Patients With Massive Pulmonary Embolism: A Randomized Clinical Trial FORPE - Leontyev, Stanislav G.; Yarovaya, Elena B.; Kutsenko, Vladimir A.; Ivlev, Oleg E.; Soplenkova, Anna G.; Semenov, Andrey M.; Semenov, Mikhail P.; Ivanov, Sergey V.; Romashova, Yulia A.; Markin, Sergey S. (Health science reports, 2025)
ABSTRACT Background and Aims Major bleedings are the most limiting factor of the usage of thrombolytic agents in pulmonary embolism (PE), especially in elderly patients. Non‐immunogenic staphylokinase is a recombinant staphylokinase with high thrombolytic activity, fibrin selectivity, and low immunogenic properties. We performed a post hoc analysis of safety outcomes in elderly patients with massive PE over 60 years' old who received non‐immunogenic staphylokinase in FORPE trial. Methods A randomized, open‐label, multicenter, parallel‐group, noninferiority FORPE trial was conducted at 23 clinical sites in Russia. A total of 310 patients aged 18 years and older with massive PE proven by computed tomography pulmonary angiography, right ventricular dysfunction, and hemodynamic instability were included. The patients were randomized for treatment either the non‐immunogenic staphylokinase (15 mg) or alteplase (100 mg). Safety outcomes were hemorrhagic stroke, bleeding types 3 and 5 according to BARC classification within 7 days after randomization. Results No cases of hemorrhagic stroke or major bleeding were registered in the non‐immunogenic staphylokinase group, whereas there were five incidences (5%) of BARC type 3 + 5 bleedings in the alteplase group (p = 0.03). All major bleedings and fatal hemorrhagic stroke in patients treated with alteplase were registered only in elderly patients over 60 years old. Conclusion The FORPE trial showed that the treatment of massive PE with hemodynamic instability with the non‐immunogenic staphylokinase was safe in elderly patients over 60 years and can be used in emergency medicine in the real‐world clinical practice. Future trials and PE registries are needed to make a final decision on safety of thrombolytic therapy with the non‐immunogenic staphylokinase in elderly patients. Trial Registration: ClinicalTrials.gov (NCT04688320). Summary Pulmonary embolism (PE) is globally one of the leading potentially fatal disease. For patients with massive PE and hemodynamic instability the thrombolysis can be life‐saving. Major bleedings are the most limiting factor of the usage of thrombolytic agents in PE, especially in elderly patients. New safe and effective thrombolytics are needed for treatment of massive PE. A post hoc analysis of safety outcomes of non‐immunogenic staphylokinase in elderly patients with massive PE and hemodynamic instability in FORPE clinical trial was performed.